Keefektifan Media Flashcards dalam belajar Kosakata Bahasa Mandarin pada siswa usia 7-8 tahun di Pusat Bahasa Mandarin Makassar - Mir'ah Azizah (Universitas Negeri Makassar, 2022)
This research was conducted to measure the effectiveness of Flashcards media in learning Chinese vocabulary. This study applies the Quantitative-Qualitative Research method in quadrant I by using a pre-test to measure students' abilities before flashcards are applied in learning Chinese, Media Flashcards, Post-test to measure students' abilities after learning Chinese by using Flashcards, and guidelines of observations in Research Instruments. The sample of this study was 15 students aged 7-8 years at the Brilliant Mandarin Language Center. Based on the results of the research, the students were very enthusiastic in learning Chinese vocabulary using flashcards and the class atmosphere became very pleasant. In addition, students' ability to master Chinese vocabulary has increased after applying flashcards. The mean score of students in the pre-test was 47.5 which was in the very poor score classification. After the flashcards were applied in learning Mandarin, the general average of the students in the Post-test was 81.25 which was classified as a very good score. This shows that the use of flashcards media is very effective in learning Chinese vocabulary. keyword: Chinese language, vocabulary, flashcards.